Community acquired pneumonia - Salas-Lopez , Juan A. (2020)
Community-acquired pneumonia is an infectious disease of the lung parenchyma, prevalent in our country with partial identification of etiological agents. It is the result of the interaction of the inflammatory process and infectious agents, with impact on the respiratory physiology with clearly identified risk factors. The diagnosis is based on clinical and radiological aspects. It requires a rational use of antibiotics, in an era of bacterial resistance. In the present symposium, definition and epidemiology are considered, with emphasis on national microbiology. In the diagnosis section, it focuses on clinical, radiological, etiological and laboratory tests. In therapy it is based on 3 aspects: degree of severity, identification of risk factors for specific agents and resistance. Control during the evolution of the disease and complications are alsoevaluated. Emphasis is placed on preventive aspects.